If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(15) = y + -6 Reorder the terms for easier multiplication: 15x = y + -6 Reorder the terms: 15x = -6 + y Solving 15x = -6 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '15'. x = -0.4 + 0.06666666667y Simplifying x = -0.4 + 0.06666666667y
| 5x-(4x+5)=0 | | x=.5x(5+6) | | 7+47z=14z | | 126=-6(4n-1) | | 20y-3=14y+12 | | -9(-5x-14)=-369 | | 9x+5x+4+8=4x+4+9x | | 3(5x+4)=5x+14 | | 12x=y+60 | | 55x+21+17x=156 | | 8c=88 | | x^5-2x^4+7x^3+8x^2-16x+56=0 | | -8y+3=-9y+4 | | 5x-22+x+31= | | -7x+8+11x-6x= | | -n-14=1-6n+2n | | 2(a+2)-5(2a-3)=3x | | 441=-9(-9x+14) | | x(4x-2)+x(2x-4)=(6x+8)(x-2) | | (2x-16)(x^2+11x+28)=0 | | -1+6r=6r-1 | | 5x-22-x+31= | | 2x-5-3x+1-3=0 | | x+(x+24)=52 | | 7x+9x-4x=9+3 | | 3(y+4)=2y+13 | | -1=2-5m-3 | | -2(5y-4)-y= | | 13x+36=9x | | 8x^2+14x-49=0 | | 1/2(16-6x)=15-1/3(9+15x) | | 4d+19=-2(d-5)-9d |